2014
DOI: 10.1159/000357428
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Aphasia Outcome after Intravenous Recombinant Tissue Plasminogen Activator Thrombolysis for Ischemic Stroke

Abstract: Introduction: No data about the specific outcome of aphasia after thrombolysis are available. Our aim was to describe the severity and type of aphasia after stroke thrombolysis. Methods: This retrospective cohort study included consecutive aphasic patients hospitalized in the Stroke Unit of Dijon (University Hospital, France) between 2004 and 2009 for a first-ever ischemic stroke of the left middle cerebral artery. Aphasic syndromes and their severity (French version of the Boston Diagnostic Aphasia Examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…This shift from abnormal right lateralized activation was likely associated with moderate reperfusion of the left FG. This mechanism has been reported in previous studies of stroke recovery (e.g., Hillis et al, 2002, 2006; Jacquin et al, 2014), and was confirmed for MMY in a recent work which reported that there was reperfusion of the PCA territory by the sub-acute phase (T2) (i.e. MMY had normal perfusion by T2, see P1 Sebastian et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This shift from abnormal right lateralized activation was likely associated with moderate reperfusion of the left FG. This mechanism has been reported in previous studies of stroke recovery (e.g., Hillis et al, 2002, 2006; Jacquin et al, 2014), and was confirmed for MMY in a recent work which reported that there was reperfusion of the PCA territory by the sub-acute phase (T2) (i.e. MMY had normal perfusion by T2, see P1 Sebastian et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…It is commonly understood that the bulk of cognitive, motor, or language recovery occurs within the acute and sub-acute phases post stroke (e.g., Kelly-Hayes et al, 1989). With respect to language function, this early post stroke recovery is thought to be primarily associated with a reperfusion of the indirectly damaged brain areas (e.g., Hillis et al, 2002, 2006; Jacquin et al, 2014). Late recovery of language function (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Reorganization is assumed to reflect neuroplasticity. Early recovery from vascular aphasia syndromes is likely attributable to restoration of blood flow (Hillis & Heidler, 2002; Jacquin et al, 2014; Marsh & Hillis, 2006), whereas later recovery may be attributable to reorganization in which other areas of the brain take over the functions of the damaged region (Fridriksson, Richardson, Fillmore, & Cai, 2012; Hillis, 2007; Jarso et al, 2013; Saur et al, 2006). For a detailed review see (Anglade, Thiel, & Ansaldo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thrombolysis contributes to this early recovery. Indeed, a retrospective observational study of two patient groups (those who received vs. those who did not receive thrombolysis) has shown that rtPA treatment improves the prognosis of aphasia at one week and three months after the stroke . Moreover, recanalization is associated with a decrease of several NIHSS scores at 24 h, including those composing the CVS .…”
Section: Discussionmentioning
confidence: 99%